Reinterpretasi Hadis Tentang Moderasi Beragama dengan Pendekatan Ma‘Anil Hadis - Nurhidayanti, Nurhidayanti; Mu’jizat (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Studies on religious moderation from the perspective of hadith have tended to emphasize textual understanding and identification of moderation values, while studies that reinterpret hadith contextually through the Ma‘ānī al-Ḥadīṡ approach are still limited. This study aims to analyze and reinterpret hadiths on religious moderation by integrating textual, intertextual, and contextual analysis. This study uses a qualitative approach through library research with data sources in the form of hadith, books of discourse, and relevant academic literature. The results show that the Ma‘ānī al-Ḥadīṡ approach produces an understanding of religious moderation that does not stop at the prohibition of excessive behavior, but includes a broader value construction of balance (tawāzun), justice (‘adl), tolerance (tasāmuḥ), and proportionality in practicing religious teachings. The main findings of this study indicate that contextual interpretation of the hadith allows the values ​​of moderation to be transformed from normative principles into an ethical framework relevant to the dynamics of contemporary socio-religious life. Thus, the Ma‘ānī al-Ḥadīṡ approach makes a methodological contribution in broadening the understanding of the hadith on religious moderation while strengthening its relevance in facing the challenges of extremism and the plurality of modern society.